(untitled) (The Review of Diabetic Studies, 2024)
Background: One of the major challenges of medical education is the lack of consensus on the best method of learning and integrating nutrition into clinical practice. The literature on nutrition education reveals a gap in the development of innovative teaching models to enhance clinical nutrition knowledge and training. Over nutrition plays a vital role in the development of a spectrum of non-communicable diseases. Diet-related disorders have a huge impact on personal health as well as the country’s economy for the management of such disorders. Globally, 11 million deaths are attributable to suboptimal diet annually. Furthermore, in 2014, more than 1.9 billion adults were overweight, while 462 million were underweight. This coexistence of under nutrition, along with overweight and obesity, or diet-related chronic diseases, is referred to as the double burden of malnutrition. This burden is universal and presents an imperative to improve the nutrition capacity of the health workforce. Nutrition is a powerful tool for the prevention and management of diet-related chronic diseases, the nutrition-related components of diseases including cancer, obesity, and diabetes are frequently not adequately addressed in actual physician practice Aim of this systematically review: To evaluate the primary healthcare physicians’ nutrition competency, Saudi Arabia 2024. Methods: A systematic review was conducted. We searched PubMed, Web of Science, Science Direct, EBSCO, and the Cochrane library. Using QCRI, study articles were first screened by title and abstract before a full-text analysis was done. Results: The usability and outcome of Self-Perceived Nutritional Competency of Primary Healthcare Physicians in Saudi Arabia are based on Vision 2030. 6 articles were selected that compliant with the theme of this present systematic review (Table 1). Conclusion: Primary Healthcare Physicians need to improve their nutritional competency knowledge, this will allow them to get the most level of nutritional knowledge and skills to provide individuals with the suitable nutritional recommendations and also successfully support patients to enhance their dietary behaviors and health conditions. PHC physicians should have continuous nutrition educational training programs to ensure the continuous provision of sound nutritional advice to patients and the public leading to a positive impact on public health.